2016
DOI: 10.1007/s13593-016-0378-6
|View full text |Cite
|
Sign up to set email alerts
|

Rooftop production of leafy vegetables can be profitable and less contaminated than farm-grown vegetables

Abstract: Urban agriculture may solve issues of feeding urban populations. In China, for example, densely packed mega cities will continue to expand in number and size, necessitating increasing food miles. Interestingly, it has been estimated that the total rooftop space in China is about 1 million hectares, some of which can be converted for rooftop farming. Yet, despite some favorable reports on urban farming, the Chinese commercial sector has shown little interest. This may be explained by the dearth of data comparin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 18 publications
(26 reference statements)
1
18
0
1
Order By: Relevance
“…[ 40 ] It has the advantage of utilizing existing land in cities to sustainably produce food locally. [ 41 ] Thus, rooftop farming potentially reduces the carbon footprints from air/land transportation of food supply from distant rural farms and consequently leading to a positive impact on the environment. [ 42 ] As SmartFarm device is a fully automated system that uses only renewable energy and harvests atmospheric water for irrigation, it eliminates the need for human resources to operate and bring down the freshwater usage for agriculture.…”
Section: Methodsmentioning
confidence: 99%
“…[ 40 ] It has the advantage of utilizing existing land in cities to sustainably produce food locally. [ 41 ] Thus, rooftop farming potentially reduces the carbon footprints from air/land transportation of food supply from distant rural farms and consequently leading to a positive impact on the environment. [ 42 ] As SmartFarm device is a fully automated system that uses only renewable energy and harvests atmospheric water for irrigation, it eliminates the need for human resources to operate and bring down the freshwater usage for agriculture.…”
Section: Methodsmentioning
confidence: 99%
“…Heavy metals enter and accumulate gradually in the human body through diet uptake. Numerous studies have shown that heavy metal pollution is widely spread in animal and plant products, aquatic products, and various processed foods all over the world (Dadar et al, 2016;Liu et al, 2016;Wijayawardena et al, 2016). Heavy metals that enter the human body through chronic exposure are very difficult to metabolize or decompose, so they accumulate in all tissues and organs over the years and exert chronic damage to the body when they reach a certain threshold (Raehsler et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…[30], type of pollutant, type of plant and soil organisms [31]. An effect of urban pollution is described for different forms of urban agriculture using uncontaminated soils at natural levels trace metals concentrations [32], hydroponic system on rooftop [33] or urban contaminated soils [34,35]. However, to our knowledge the quality of vegetables grown on Technosols made with by-products derived from urban wastes was not informed.…”
Section: Introductionmentioning
confidence: 99%